2009
DOI: 10.1186/1475-2867-9-4
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to cisplatin does not affect sensitivity of human ovarian cancer cell lines to mifepristone cytotoxicity

Abstract: Background: The prototypical antiprogestin mifepristone exhibits potent growth inhibition activity towards ovarian cancer cells in vitro and in vivo. The aim of this research was to establish whether mifepristone is capable of inhibiting cell proliferation and inducing apoptotic cell death regardless of the degree of sensitivity ovarian cancer cells exhibit to cisplatin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(49 citation statements)
references
References 52 publications
(64 reference statements)
3
46
0
Order By: Relevance
“…Antiprogestin mifepristone is toxic towards ovarian cancer cells, with cytostasis manifested at lower micromolar concentrations and lethality taking place when the compound is used at higher micromolar doses (Freeburg et al,2009a;Goyeneche et al,2007;Goyeneche et al,2011;Tieszen et al,2011). When mifepristone was used at doses up to 20 M, the effect was limited to cytostasis demonstrated by the reversibility of the growth inhibition observed when the drug was removed from the culture media, in association with the lack of measurable cell death (Goyeneche et al,2007).…”
Section: Mifepristone-induced Cytostasis Vs Lethality In Ovarian Canmentioning
confidence: 99%
See 2 more Smart Citations
“…Antiprogestin mifepristone is toxic towards ovarian cancer cells, with cytostasis manifested at lower micromolar concentrations and lethality taking place when the compound is used at higher micromolar doses (Freeburg et al,2009a;Goyeneche et al,2007;Goyeneche et al,2011;Tieszen et al,2011). When mifepristone was used at doses up to 20 M, the effect was limited to cytostasis demonstrated by the reversibility of the growth inhibition observed when the drug was removed from the culture media, in association with the lack of measurable cell death (Goyeneche et al,2007).…”
Section: Mifepristone-induced Cytostasis Vs Lethality In Ovarian Canmentioning
confidence: 99%
“…We showed that cell cultures exposed to mifepristone after cisplatin had a remarkable increase in the percentage of cells expressing the cell death marker cleaved poly (ADP-ribose) polymerase (PARP) and the mitotic marker phospho-histone H3 suggesting that mifepristone potentiates cisplatin lethality and that the cells likely die as a consequence of mitotic failure (Freeburg et al,2009b). We also reported that the effect of mifepristone in ovarian cancer cells is independent of p53 functionality and platinum sensitivity (Freeburg et al,2009a), making mifepristone an even more interesting chemotherapeutic candidate for ovarian cancer as the majority of tumors in relapsing patients are platinum resistant and p53 mutant (Ozols,2006b). Finally, we have shown in ovarian cancer cells that mifepristone potentiates the lethality of otherwise sub-lethal doses of cisplatin, and synergizes with cisplatin growth inhibiting ovarian cancer cells of different genetic backgrounds and platinum sensitivities (Gamarra-Luques&Telleria,2010).…”
Section: Mifepristone In Ovarian Cancer Therapeuticsmentioning
confidence: 99%
See 1 more Smart Citation
“…In each case, the intrauterine administration resulted in the characteristic inhibition of normal menstrual bleeding, atrophy of endometrial spiral arterioles and functionalis thickness, consistent with observations from systemic administration (Figure 2). The mechanism of attenuation of estradiol effects on the endometrium is not well understood, and although steroidal PRAs appear to block cell proliferation in various in vitro cell-based systems, the concentrations needed for this effect are considerably greater than those which elicit the effect in vivo (Freeburg et al, 2009a;Goyeneche et al, 2007;Murphy et al, 2000;Ohara et al, 2007;. One clue to a potential mechanism has emerged from observations of elevated endometrial androgen receptor (AR) expression (Narvekar et al, 2004;Slayden & Brenner, 2003) following PRA administration and the known effects of AR modulators (e.g.…”
Section: Macaquementioning
confidence: 99%
“…Cells were then counted in a Neubauer haemocytometer chamber using a clear-field microscopy. Concentration of extract needed to achieve 50% of growth inhibition is indicated as IC 50 , while extract concentration where 50% cell death was observed is indicated as LC 50 [15,16]. Assays were performed three times in triplicate.…”
Section: Dye Exclusion Assaymentioning
confidence: 99%